Regole invisibili - Eligio Resta (Quaderni di Sociologia, 1993)
Illegal behaviors are concerned with “legal-illegal” code. This essay focuses the differentiation between ethical, political and legal systems. Illegal behaviors 184 have to be seen from the point of view of systemic communications. The phenomenon is produced in the social system and in the social system is regulated. Community involvment, moral perception and legal control are all relevant but quite different. Adequate reactions and correct answers depend on adequacy of communication.